2018
DOI: 10.1002/admi.201701659
|View full text |Cite
|
Sign up to set email alerts
|

Dodecylamine‐Induced Synthesis of a Nitrogen‐Doped Carbon Comb for Advanced Lithium–Sulfur Battery Cathodes

Abstract: cycling life, significant self-discharge, and decreased Coulombic efficiency of the batteries. [3][4][5] The second is the inherent poor electrical conductivity of the sulfur that often results in unsatisfactory rate capabilities and the poor utilization of sulfur. [6][7][8] To tackle the first issue, tremendous efforts have been made to develop a facile approach to realize the physical confinement of soluble sulfur species within the pores of nonpolar hydrophobic carbon materials, such as highly ordered mesop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…As shown in Figure S1E, the sharp nitrogen uptake at a low relative pressure region (p/p 0 < 0.1) and the obvious hysteresis at a moderate relative pressure region (p/ p 0 > 0.45) implies the existence of micropore and mesopore, respectively. 31,32 The pore size distribution of CC-A was calculated by Barrett-Joyner-Halenda equation from adsorption curve, showing the overall pore size of smaller than 10 nm and average pore size of about 2.2 nm ( Figure S1F). The pore volume was calculated to be 0.13 cm 3 /g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure S1E, the sharp nitrogen uptake at a low relative pressure region (p/p 0 < 0.1) and the obvious hysteresis at a moderate relative pressure region (p/ p 0 > 0.45) implies the existence of micropore and mesopore, respectively. 31,32 The pore size distribution of CC-A was calculated by Barrett-Joyner-Halenda equation from adsorption curve, showing the overall pore size of smaller than 10 nm and average pore size of about 2.2 nm ( Figure S1F). The pore volume was calculated to be 0.13 cm 3 /g.…”
Section: Resultsmentioning
confidence: 99%
“…From the high-resolution C 1s XPS spectrum in Figure 2C, five peaks with bond energies of 284.6, 285.6, 286.5, 288.2, and 291.4 eV are observed, which can be identified to the C-C, C-N/C-O, C═N/C═O, O═C-O, and π-π*, respectively. 31,35 The presence of C and N bonds in XPS demonstrated nitrogen was successfully incorporated into the structure of carbon nanotubes during the growth of carbon nanotubes via chemical vapor deposition. It was suggested that the ORR activity of carbon materials is greatly affected by the configuration of the C and N bonds in their structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al designed a new dodecylamine micelle-induced nitrogen-doped carbon comb (NCC) as sulfur host. [154] This nitrogen-doped NCC substantially increased the conductivity of cathodes and introduced the chemical anchoring toward polysulfides, effectively suppressing the losses of sulfur species upon cycling. As a result, NCC with a high loading of sulfur achieved an impressive cycling lifespan and rate performance.…”
Section: Heteroatom-doped Carbonmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Previous reports on the synthesis of carbon IOs have detailed the use of complex precursors, which oen require convoluted processing procedures. These include, HF etching to remove the template material, 24,25 chemical vapor deposition for template inlling, 26 and the use of toxic carbon-precursors, including a phenol-formaldehyde resorcinol, a mixture of furfuryl alcohol and oxalic acid, and bis-ortho-diynyl arsene (BODA) monomers. [27][28][29][30][31] The aim of this study is to simplify the synthesis procedure for carbon IOs.…”
Section: Introductionmentioning
confidence: 99%